Structural Finite Element Analysis of REBCO Tape Delamination with Solid-Shell Element under Various Loads. Issue 1 (1st May 2022) - Zhao, Zijia; Moore, Peter; Chiesa, Luisa
Abstract: Structural Finite Element Analysis was performed to study the delamination behaviour of layer laminated REBCO tapes using a Solid-Shell element under various loading conditions, including (1) transverse tensile delamination, (2) shear delamination and (3) peeling delamination. A Solid-Shell element is well suited to simulate REBCO tape because the material and thickness of all the layers can be specified within a single element. The results obtained from the models utilizing Solid-Shell elements are compared to a more computationally intensive method known as Cohesive Zone Method (CZM), which has successfully modelled the initiation and propagation of REBCO's delamination [1]. The results show that the stress state of REBCO tape in transverse tensile and shear directions can be accurately captured by the proposed method employing Solid-Shell elements if the transverse tensile and shear delamination stress is measured experimentally for a specific REBCO and used as failure criteria. In this work, the failure criteria adopted from previous experimental studies are 50 MPa in the transverse tensile direction and 10 MPa in the shear direction. This work provides a time-efficient modelling tool to predict and mitigate delamination in REBCO tapes used in complex systems.